Attitude Assessment Analysis on Islamic Education Learning at Junior High School Level in The Application of Curriculum 2013 - Khafidhotul Baroroh; Andi Prastowo; Sarjono Sarjono (AIUA Journal of Islamic Education, 2021)
In the 2013-2014 academic year, the 2013 curriculum has begun to be tested, the 2013 curriculum consists of teachers measuring all aspects of development. Starting from the cognitive (knowledge), affective (attitude) and psychomotor (skills) aspects. The evaluation of these three aspects must be carried out by the teacher himself. The 2013 curriculum is determined by a table determined by spiritual attitudes and attitudes. The purpose of this study was to examine the learning attitudes of Islamic Education in the 2013 curriculum, this study used a library research method. The results of this study indicate: 1) in the process of handling attitudes the authorities are not only Islamic education teachers, counseling teachers or homeroom teachers, but students can also perform the process of measuring attitudes through peer-to-peer techniques. 2) the 2013 dwarf process includes several techniques. First, the observation technique, this technique is the main technique that must be done, the observation technique uses two tools, namely observation sheets and journals. Second, production costs and production costs, both of these techniques are supporting factors.